Phage Infection in Vaginal Lactobacilli: An In Vitro Study - Pavlova, Sylvia I. (Hindawi Publishing Corporation, 1997)
Objective: During bacterial vaginosis, an unexplained decrease of vaginal lactobacilli occurs. To identify whether these lactobacilli could be infected by phages, we isolated phages from vaginal lactobacilli and analyzed their potential virulence in attacking vaginal lactobacilli in vitro. Methods: Vaginal samples were obtained from 39 reproductive-aged women. The selective Rogosa SL agar was used to isolate lactobacilli, from which phages induced by mitomycin C or released spontaneoulsy were analyzed by the agar spot method. Results: Of 20 samples from women with vaginal infections, 12 did not have lactobacilli. From the remaining 8 infection samples and the 19 samples from healthy women, 37 Lactobacillus strains were isolated, from which 7 temperate phages were identified. Upon analysis, all 7 phages infected vaginal lactobacilli from the same and/or different women in vitro. Two phages, Φkc005 and Φkc007, had a broad host range, infecting 7 of 8 species tested. A control intestinal Lactobacillus phage also lysed several vaginal strains. One vaginal phage, Φkc039, was apparently lytic against vaginal lactobacilli from 7 other women. This phage was characterized as follows: plaque morphology, small and clear; burst size, 300 phages per cell; spontaneous induction rate, 1 per 10(6) cells; DNA, double-stranded and linear, 41 kb; and shape, a hexogonal head and a non-contractile tail. Conclusions: Bacteriophages were isolated from vaginal lactobacilli of some women and were shown in vitro to lyse vaginal Lactobacillus strains from the same and/or different women. It was suggested that vaginal lactobacilli might be suppressed by phages.